THE QUALITY OF EARNINGS WITH FACTORS - DIRVI SURYA ABBAS; ARRY EKSANDY; MULYADI; HANIFAH NADA SAUSANTI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This study aims to determine the effect of earnings persistence, internal audit quality and investment opportunity set on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The research period used was 5 years, namely the 2014-2018 period. The study population includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained 6 company samples. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX) website. The data analysis method used is panel data regression analysis processed using the help of E-views software Version 9. The results showed that earnings persistence affected earnings quality, internal audit quality did not affect earnings quality, and investment opportunity set did not affect earnings quality.